2016 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE) 2016
DOI: 10.1109/tale.2016.7851774
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating student and staff engagement across multiple offshore campuses for transnational education using an immersive video augmented learning platform

Abstract: Opportunities in transnational education have been growing across the higher education sector. The incentive for institutions to explore opening offshore satellite campuses includes access to more students and building the institutions reputation across the globe. A number of risks are also associated with transnational education, especially in terms of quality. It is important that students across all campuses receive the same high standard of education. That is, students at offshore campuses should not be pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In particular Q2 indicates that the platform is effective for verbal communication, one of the key limitations in [3]. The responses show that the participants believed that V-PASS provided a good sense of presence, allowed collaboration to occur and was an effective way of teaching course related content, providing some agreement with the findings in [10][11][12]. This does provide some confidence in using iSee to trial a transnational V-PASS session if a way to encourage student participation could be found.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…In particular Q2 indicates that the platform is effective for verbal communication, one of the key limitations in [3]. The responses show that the participants believed that V-PASS provided a good sense of presence, allowed collaboration to occur and was an effective way of teaching course related content, providing some agreement with the findings in [10][11][12]. This does provide some confidence in using iSee to trial a transnational V-PASS session if a way to encourage student participation could be found.…”
Section: Resultssupporting
confidence: 55%
“…The study found students thought iSee was easier to use due to its similarities with gaming and that team collaboration was better due to the focus of face to face communication. This was followed up by a number of other studies [10][11][12] that found that the video avatar substantially contributed to the acceptance and quality of engagement online; and provided a mechanism to facilitate transnational education. Therefore, this pilot study investigates if iSee is a suitable technology for running a virtual PASS (V-PASS) scheme at a traditional face to face university that could then be expanded to include students from other trans-national satellite campuses.…”
Section: Introductionmentioning
confidence: 96%